γδ T/Interleukin-17A Contributes to the Effect of Maresin Conjugates in Tissue Regeneration 1 on Lipopolysaccharide-Induced Cardiac Injury - Yang, Yi; Li, Xin-Yu; Li, Lin-Chao; Xiao, Ji; Zhu, Yin-Meng; Tian, Yang; Sheng, Yong-Mao; Chen, Yan; Wang, Jian-Guang; Jin, Sheng-Wei (Frontiers in Immunology, 2021)
The mechanisms underlying sepsis-induced cardiomyopathy (SIC) remain poorly understood and there are no specific therapeutics for SIC. We investigated the effects of maresin conjugates in tissue regeneration 1 (MCTR1) on SIC and explored its potential mechanisms. The experiments were conducted using an endotoxemia model induced by lipopolysaccharide (LPS). Mice were given MCTR1 intravenously 6 hours after LPS stimulation. Echocardiography was performed to assess cardiac function 12 hours after LPS administration. Treatment with MCTR1 significantly enhanced cardiac function and reduced LPS-induced increase of mRNA expression levels of inflammation cytokines. Transcriptomic analysis indicated that MCTR1 inhibited neutrophil chemotaxis via the IL-17 signaling pathway. We confirmed that MCTR1 reduced the expressions of neutrophil chemoattractants and neutrophil infiltration in the LPS-stimulated hearts. MCTR1 also resulted in a considerable reduction in IL-17A production mainly derived from γδ T cells. Moreover, our results provided the first evidence that neutralizing IL-17A or depletion of γδ T cells markedly decreased neutrophil recruitment and enhanced cardiac function in LPS-induced cardiac injury. These results suggest that MCTR1 alleviates neutrophil infiltration thereby improves cardiac function in LPS-induced cardiac injury via the IL-17 signaling pathway. Thus, MCTR1 represented a novel therapeutic strategy for patients with SIC.